Isolation of Fungal Endophytes from Melastoma malabathricum L. and Their Potential as Antifungal - Rusi Octavianti; Israwati harahap; Elsie Elsie (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2017)
The aim of this study was to isolation the endophytic fungi from medicinal plant Melastoma malabathricum L. and to investigate their potential antifungal activity. Isolation endophytic fungi was carried out using surface sterilized method. The fungal extracts were assessed for antifungal activity against Candida albicans using agar well diffusion method. A total of 28 isolates fungal endophytes from leaves, stems, flowers and roots of Melastoma malabathricum L. The results showed that of twelev have strong category within inhibit growth of C. albicans. Isolate 18 is endophytic fungi who produced the largest zones of inhibit is 19 mm.